Combined use of Calciprill and sodium silicate improves low pH soil chemical properties - Ng, Ji Feng; Ahmed, Osumanu Haruna; Omar, Latifah; Jalloh, Mohamadu Boyie; Kwan, Yee Min; Poong, Ken Heong; Musah, Adiza Alhassan (Multidisciplinary Digital Publishing Institute, 2021)
The highly weathered, acidic tropical soils are generally less fertile because of their low pH, high exchangeable acidity, and Al, Fe, and Mn saturations. Using soil amendments to solve the aforementioned problems is essential. To this end, Calciprill and sodium silicate are worth considering because of their high neutralizing value and dissolution to suppress exchangeable acidity and Al, Fe, and Mn hydrolysis, while at the same time increasing soil pH to improve the availability of inorganic N, available P, exchangeable base cations, and Effective Cation Exchange Capacity (ECEC). An incubation study was conducted to determine the right combination of Calciprill and sodium silicate to reduce exchangeable acidity and Al and Fe hydrolysis to improve inorganic N, available P, exchangeable base cations availability, and ECEC. Bekenu series (Typic Paleudults) was incubated with a combined use of Calciprill at 80%, 90%, and 100% Ca saturations and sodium silicate at 90, 105, 120, 135, and 150 kg ha−1 for 40, 80, and 120 days, respectively. The laboratory incubation study was carried out using a Completely Randomized Design (CRD) with triplicates to determine the aforementioned treatment effects of the combined use of Calciprill and sodium silicate on soil pH, exchangeable, Al, inorganic N, available P, electrical conductivity, exchangeable cations (K, Ca, Mg, Na, Fe, and Mn), and ECEC using standard procedures. Soils with both amendments significantly increased soil inorganic N, available P, electrical conductivity, exchangeable base cations (K, Ca, Mg, and Na), and ECEC. This was because the amendments increased soil pH by suppressing exchangeable acidity. Moreover, they transformed Al, Fe, and Mn ions into insoluble compounds such as Al and Fe hydroxides and Mn oxides because of their high inherent exchangeable cations, especially Ca and Na. This suggests that the combined use of Calciprill and sodium silicate can enhance soil productivity. The most suitable combination is 7.80 g Calciprill and 9.26 g sodium silicate (C3S5) per one kilogram soil. Additionally, the findings provide fundamental information for future greenhouse and field trials to determine the effects of the suitable combination of the amendments uncovered by this present study on soil health and crop productivity.